The impact of a school garden program on children's food literacy, climate change literacy, school motivation, and physical activity: A study protocol. - Anna Stage; Marie Caroline Vermund; Mads Bølling; Camilla Roed Otte; Alberte Laura Oest Müllertz; Peter Bentsen; Glen Nielsen; Peter Elsborg (PLoS ONE)
Objective FoodACT aims to investigate how school gardens affect children's food literacy (FL), climate change literacy (CCL), school motivation (SM), and physical activity (PA). Design It comprises a multimethod, quasi-experimental inquiry into an existing Danish school garden program, Gardens to Bellies (GtB). Data will be collected using surveys, accelerometry, semi-structured and focus-group interviews. The study is preregistered with ClinicalTrials.gov (#NCT05839080). Setting Six GtB school garden locations across Region Zealand and Region of Southern Denmark. Participants Fourth grade pupils attending GtB (approx. 1600) are recruited to the intervention group. Fourth grade pupils from schools not attending GtB (approx. 1600) are recruited to the control group. Intervention Pupils grow, prepare and cook foods for meals in the school garden during eight garden sessions. Main outcome measures FL, CCL and SM are measured using pre- and post-intervention surveys in both groups. Pupils participating in GtB have their PA assessed using accelerometery, and acute SM by text-message-surveys. Semi-structured and focus-groups interviews are held with garden facilitators and pupils focusing on the implementation of GtB and mechanisms related to developing FL and CCL. Analysis The effect on FL, CCL and SM is assessed using linear mixed models. PA and acute SM are assessed by comparing data on days with and without GtB in a subsample of 900 pupils. Qualitative data will be analysed using thematic analysis.